Role of homeostatic plasticity in critical brain dynamics following focal stroke lesions - Rodrigo P. Rocha; Marco Zorzi; Maurizio Corbetta (Scientific Reports, 2024)
Abstract Can focal brain lesions, such as those caused by stroke, disrupt critical brain dynamics? What biological mechanisms drive its recovery? In a recent study, we showed that focal lesions generate a sub-critical state that recovers over time in parallel with behavior (Rocha et al., Nat. Commun. 13, 2022). The loss of criticality in a cohort of stroke patients was associated with structural brain disconnections, while its recovery was accompanied by the re-modeling of specific white-matter tracts. These results were challenged by Janarek et al. (Sci. Rep. 13, 2023), who proposed an alternative interpretation for the anomalous monotonic decaying of the second cluster size, which is the neural signature originally used to infer loss of criticality. The present study tackles this controversy and provides evidence that the theoretical framework proposed by Janarek et al. cannot explain the anomalous cluster dynamics observed in our patients. Notably, this invalidates the claim that the brain maintains its critical dynamics regardless of the lesion severity. In addition, we explore biological mechanisms beyond white-matter remodeling that may facilitate the recovery of criticality over time. We considered two distinct scenarios: one where we suppress homeostatic plasticity, and another where we increase the excitability of brain regions. We find that suppressing homeostatic plasticity - specifically, the inhibition-excitation balance - disfavors the emergence of criticality. Conversely, increasing brain excitability can help to restore criticality when the latter is disrupted. Our results suggest that normalizing the excitation-inhibition balance is crucial for supporting recovery of critical brain dynamics.